renovations - Grigoryeva, Elena (project baikal, 2017)
There is a Latin tag “cui prodest?” meaning “who stands to gain?”. When it is not immediately apparent which political or social groups, forces or alignments advocate certain proposals, measures, etc., one should always ask: “Who stands to gain?”. (V. I. Lenin, Who Stands to Gain?)An unsettling problem of the future renovation of the certain generation of houses aroused in the late spring in Moscow and spread immediately around Russian cities, since, as you know, khrushchevki can be found everywhere. However, the need for renovation is felt differently in different parts of the country. The question where to put the comma in the sentence “Demolition impossible to restore” is solved in Moscow by voting among residents. In Pribaikalie, a region of high seismic activity, the problem of reconstruction of the first prefabricated series is very acute.Project Baikal returns to the question which was raised in one of the previous issues in the early spring, anticipating a surge in interest (see PB 51, pp 54-161. Renovation of the Panel House-Building of the 1960-1980s in Germany).
Keywords: renovation; Pribaikalie; panel house-building